Fallos en el filtraje de información auditiva en esquizofrenia: ¿disfunción de cortezas uni o heteromodales? - Paz, R. D.; Ortiz, T.; Cañive, J. M. (Actas Espanolas de Psiquiatria, 2007)
Failure filtering out redundant auditory information is the most replicated neurophysiological abnormality observed in patients with schizophrenia. However, the brain structures involved in this deficit remains obscure. Two main hypotheses have been proposed to explain this phenomenon. The first maintains that the auditory gating deficit in schizophrenia is related to abnormal function of microcircuits within the hippocampal formation. The second hypothesis proposes that the deficit may be linked to impaired prefrontal cortex function. In both scenarios, auditory gating is conceptualized as a process dependent on the functional indemnity of cortical areas that integrate information from different sensory modalities. When filtering out redundant information, heteromodal cortices (hippocampal formation or prefrontal cortex), ensure that redundant stimuli do not reach higher-order levels of information processing in the brain and do not interfere with working memory performance. Findings from our lab, using magnetoencephalography (MEG), and data from other labs using electroencephalography (EEG), suggest an alternative hypothesis. We hypothesize that auditory gating deficit in schizophrenia is due to the abnormal function of unimodal microcircuits within left auditory cortex, independent from abnormalities in heteromodal cortices. Explaining whether auditory gating deficit in schizophrenia is determined by a primary dysfunction of unimodal or multimodal cortices may help elucidate the mechanisms involved in the sensory information overload and the characteristic cognitive deficits found in this disorder.